THE INFLUENCE OF SOCIAL MEDIA MARKETING ACTIVITIES (SMMA) ON PURCHASING DECISIONS MEDIATED BY FEAR OF MISSING OUT (FOMO) AND BRAND LOVE: - Azhari, Makhyatul; Roosdhani, Mohamad Rifqy (Universitas Nusa Cendana, 2025)
This study aims to analyze the impact of social media marketing activities (SMMA) on consumer purchasing decisions at Miniso stores, with the role of brand love and fear of missing out (FOMO) as mediating variables. This study utilizes a quantitative method with a Structural Equation Modeling (SEM) approach processed through SmartPLS version 4.0. with a total of 200 miniso Jepara Kudus consumer respondents. The outcomes displayed that social media marketing activities have a significant influence on brand love as well as FOMO, both of which influence consumer purchasing decisions. This finding confirms the significance of effective social media management in constructing consumer emotional attachment and driving a sense of purchase urgency, especially in modern retail consumers such as Miniso. The implications of this study provide strategic insights for marketers in maximizing the potential of social media to increase consumer loyalty as well as purchase decisions. Keywords: Social Media Marketing Activities, Brand Love, Fear of Missing Out (FOMO), Purchase Decision